Dampak Alokasi Anggaran Dana Desa (DD) Terhadap Tingkat Kemiskinan Di Indonesia - Wido Cepaka Warih; Ariski S; Syugiarto Syugiarto (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2021)
This study aims to examine the impact of village budget allocations on poverty levels in Indonesia. By using case studies as the basis for research, literature studies as the basis for collecting data, and using the main references from previous studies related to the impact of village funds and poverty. The data used in this study is secondary data from 2015-2019 which includes APBN data (balancing funds), Village Fund Allocation (DD), and poverty data. The data analysis used is descriptive qualitative, which aims to explain the facts by using comparison and trend analysis (tables and graphs), used to analyze the relationship between village allocation funds and poverty. The results showed that the Village Fund Allocation (ADD) disbursed by the central government was 259.2 trillion in a period of 5 years (2015-2019) only reducing the poverty rate by 1.72%. In addition, the village funds disbursed did not have a significant impact. The allocation of such a large Village Fund (ADD) should be able to significantly reduce the poverty rate, which is not seen in the research that has been done